Development of a Teachmint-Based Digital Module to Improve Students’ Learning Effectiveness in Pancasila Education - Ni Wayan Sayuwaktini Sayu; Rangga Firdaus; Herpratiwi; Undang Rosidin (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze (1) the potential and conditions of development, (2) the process, (3) the product, and (4) the attractiveness of teachmint-based digital modules for students. The research method adapts Borg and Gall's research and development (R&D) with a population of class VIII students and a sample of 60 students. Data collection was done using questionnaires, observations, questionnaires, and documentation, while data analysis was done using descriptive statistical analysis techniques and t-tests. The results of the study show: (1) the potential and conditions of module development based on expert validation obtained very valid results and can be used without revision, with a percentage of material experts 90%, media experts 77.5%, and design experts 76%. (2) The process of developing teachmint-based digital learning modules showed an effectiveness level of 91%, which is included in the very effective category. (3) The product of developing teachmint-based digital learning modules has proven to be effective in improving learning outcomes with an effect size value of